Financial performance analysis of airline companies evidences from southeast asia airline industry for the period of 2013-2017 - Arif, Jumaidi; M. Daryanto, Wiwiek (The Indonesian Journal of Business Administration, 2019)
Abstract. Since 2004, the Low Cost Carriers (LCC) had tremendous growth in the Southeast Asia airline industry. Due to this condition, the Full Service Airline (FSA) market share had dropped to below 50 percent. Currently, most of FSA in SE Asia are stated-owned airlines and it becomes important due to the role as the front liner of government in tourism. Therefore, it is necessary to maintain the sustainability as the future development of the tourism industry depends on a gradual increase in air service. This research aims to analyze the financial health conditions of four airline SOEs period 2013 – 2017 and validated by the decree No. KEP-100/MBU/2002 issued by Indonesia Ministry of SOEs in June 2002. There are eight ratios analyzed: 1) Return on Equity 2) Return on Investment 3) Cash Ratio 4) Current Ratio 5) Collection Period 6) Inventory Turnover 7) Total Equity to Total Asset and 8) Total Asset Turnover. In addition, return on invested capital (ROI) results from the companies will be compared with the industry benchmark of weighted average cost of capital (WACC) to measure the company’s level of profitability The result shows that from 2013 – 2017, four airline SOEs has achieved rating as follows: SIA (BBB, BBB, BBB, BBB, BBB); HVN (BB, BB, BB, BBB, A); GIA Tbk (BBB, BB, BBB, BB, B); and THA (B, B, B, B, B). The return on invested capital (ROIC) of four stated-owned airlines were below the weighted average cost of capital (WACC) of each company. This research has added the knowledge in the financial literature. It also gives strong insights about the financial condition, therefore the company could make decisions to increase the market share and the profitability.Keywords: Airlines industry, Financial ratio analysis, the SOE decree No. KEP-100/MBU/2002, stated owned enterprises, Weighted Average Cost of Capital, Southeast Asia